2010
DOI: 10.1080/09585192.2010.528653
|View full text |Cite
|
Sign up to set email alerts
|

You're from where? The influence of distance factors on New Zealand expatriates’ cross-cultural adjustment

Abstract: This study empirically tests the influence of various distance factors on expatriate crosscultural adjustment. Expatriate perceptions of home and host country differences, objective measures of distance and the accuracy of expatriate evaluations of host country distance were compared as predictors of expatriate adjustment difficulty in the host country. The results revealed that perceived distance, objective cultural distance and the expatriate's perceptual inaccuracy had a significant effect on expatriate adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 49 publications
3
38
0
1
Order By: Relevance
“…In their research, international HR managers lamented that although organizations see training programs (typically from one to two days in duration) as beneficial, few expatriates and their accompanying family members show interest in participating in these programs. Some research has also found that expatriate training has little or no effect (Selmer, 2005) or even negative effects (Jenkins & Mockaitis, 2010) on cross-cultural adjustment of expatriates. Generic or 'one size fits all' approaches to training that neglect unique workplace demands in specific countries are in part to blame (Vance & Paik, 2002).…”
Section: Global Teams As a Cross-cultural Training Toolmentioning
confidence: 99%
“…In their research, international HR managers lamented that although organizations see training programs (typically from one to two days in duration) as beneficial, few expatriates and their accompanying family members show interest in participating in these programs. Some research has also found that expatriate training has little or no effect (Selmer, 2005) or even negative effects (Jenkins & Mockaitis, 2010) on cross-cultural adjustment of expatriates. Generic or 'one size fits all' approaches to training that neglect unique workplace demands in specific countries are in part to blame (Vance & Paik, 2002).…”
Section: Global Teams As a Cross-cultural Training Toolmentioning
confidence: 99%
“…More recently, a number of studies have focused on the significance for the adaptation process of the cultural distance between home and host countries (Hemmasi & Downes, 2013;Jenkins & Mockaitis, 2010). Generally speaking, cultural distance refers to differences between home and host cultures (Hemmasi & Downes, 2013).…”
Section: Factors Influencing Expatriate Adjustmentmentioning
confidence: 99%
“…Generally speaking, cultural distance refers to differences between home and host cultures (Hemmasi & Downes, 2013). Beyond objective differences of this kind, it has been argued that the mindset of expatriates influences the adaptation process, as in their mental image of the foreign country and the validity of this image (Jenkins & Mockaitis, 2010).…”
Section: Factors Influencing Expatriate Adjustmentmentioning
confidence: 99%
“…Geographical distance can, for example, be measured either between the capital city of the home country and the capital city of the target country (Jenkins and Mockaitis, 2010) or between the geographic centre of the home country and the geographic centre of the target country (Ojala and Tyrväinen, 2007). Certain factors connected with an increasing geographical distance have a direct impact on the individual, e.g.…”
Section: Geographical Distancementioning
confidence: 99%
“…Certain factors connected with an increasing geographical distance have a direct impact on the individual, e.g. something as simple as the duration of travel (and any associated time zone shift to the host country) can have a significant effect on the abilities to function on a day-to-day basis (Shenkar, 2001;Jenkins and Mockaitis, 2010). Hutzschenreuter et al (2011) state that "the need to bridge the distance between the loci of extant operations and new local contexts" (p. 307) is the key characteristic of international expansion.…”
Section: Geographical Distancementioning
confidence: 99%